2021
DOI: 10.4103/njs.njs_67_19
|View full text |Cite
|
Sign up to set email alerts
|

Developing a low-resource approach to trauma patient care - findings from a nigerian trauma registry

Abstract: Background: Trauma is a worldwide problem that results in significant morbidity and mortality in developing countries. Objective: This study looks at the demography of trauma from data abstracted from a Nigerian trauma registry and considers the peculiarities of a low-resource setting from this perspective. Methods: Trauma registry data from January 2013 to June 2014 were analyzed. Results: A total of 542 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…21 A review of trauma registry data revealed that injured patients arrive at the emergency department in a median time of 3 hours. 22 This was in keeping with a finding by Malomo et al, where about half of the head injured patients presented within 12 hours. 23 While our data was not specific about time to arrival, the delayed / late arrival of patients with ankle fractures in the opinion of more than two-thirds of our cohort, may be due to the injury usually not being life or limb threatening, which appears to afford time to source for funds, or due to the tendency to resort to TBS for initial care of injuries.…”
Section: Discussionsupporting
confidence: 89%
“…21 A review of trauma registry data revealed that injured patients arrive at the emergency department in a median time of 3 hours. 22 This was in keeping with a finding by Malomo et al, where about half of the head injured patients presented within 12 hours. 23 While our data was not specific about time to arrival, the delayed / late arrival of patients with ankle fractures in the opinion of more than two-thirds of our cohort, may be due to the injury usually not being life or limb threatening, which appears to afford time to source for funds, or due to the tendency to resort to TBS for initial care of injuries.…”
Section: Discussionsupporting
confidence: 89%
“… 18 Similarly in Nigeria, a high proportion of patients were transported to trauma centers by laypersons with long transport times. 19 The pattern of a high proportion of road traffic accidents and intracranial injuries among those seriously injured was also seen in a recent study in Tanzania using data from the WHO model trauma registry. 20 In cases of seriously injured patients with head injury, rapid transport to a trauma center with highest level of care provides the best opportunity for survival.…”
Section: Discussionmentioning
confidence: 69%
“…A potential solution to the drawbacks of collecting injury surveillance data is the concept of minimum data set as recommended by the Centres for Disease Control and Prevention (CDC) [52] . This concept ensures that only essential information are captured and was utilised in the development of the Kampala TR form and more recently in Nigeria, the Uyo TR form [ 53 , 54 ]. These existing TRs should be adapted by the hospitals within the region and subsequently pooled into the regional trauma registry.…”
Section: Introductionmentioning
confidence: 99%